Endogenous Meningococcal Endophthalmitis in a Well Infant - Mervat A. Qutub; Ayman A. Abd El-Azim (Journal of King Abdulaziz University: Medical Sciences, 2023)
Endogenous bacterial endophthalmitis has become a rare occurrence after the widespread use of modern antibiotics. This study reports on a healthy infant who developed meningococcal endogenous endophthalmitis at the age of five months.